Evaluasi Tata Kelola Guna Meningkatkan Kinerja Manajemen Teknologi Informasi Menggunakan Framework COBIT 5 - Fitria Febriani; Augie David Manuputty (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The Salatiga Class I District Court is a government agency that has implemented Information Technology (IT) governance which has problems in IT management, so the purpose of this study is to evaluate information technology governance using the COBIT 5 framework by determining the level of capability and gaps. The results of the recapitulation of the questionnaire with the Likert scale model obtained the average value of the selected domain getting a value of 3.28, which means that the current level of capability (as is) is at level 3 (established process), while the numbers from the range of 0 to 5 levels are expected or target (to be) namely 5 (optimization process). So that a gap or gap is obtained, namely the value of 1.27 which results in a reduction between to be and as is. The selected process domain is in the highest position, namely DSS01 with a value of 3.80 or level 4 (predictable process) while the lowest position is APO12 with a value of 2.82 or level 3 (established process). To achieve the expected conditions, the IT subdivision can improve in dealing with IT risks and IT problems that occur in the Salatiga District Court Class I B. In addition to evaluating IT governance, testing system functionality is also carried out by using the Blackbox Testing method with the Boundary Value Analysis technique. The object is used for testing the system, namely e-Court tested on the registration page and login page. From the results of system testing e-Court On the registration page, there is a discrepancy in the expected name field and on the login page that the test results field - field as expected. Keywords — Information Technology Governance; COBIT 5; e – Court; Blackbox Testing; Boundary Value Analysis.